Gut in COVID 19-is it worth noticing - Narendra S Javadekar (Wolters Kluwer Medknow Publications, 2021)
Although much has been talked and written about the respiratory menace that Coronavirus disease causes, a close examination reveals that gut symptoms are equally important diagnostic markers for COVID-19. Almost 53% of COVID-19 patients experience gastrointestinal (GI) symptoms. The entry of the SARS Cov-2 virus is mediated through angiotensin-converting enzyme receptors which are abundant in the GI tract. The virus also affects the GI tract through the gut lung axis. In addition to the GI tract epithelium, hepatobiliary and pancreatic systems are also affected in COVID through multiple mechanisms. GI manifestations vary from relatively benign symptoms such as nausea vomiting diarrhea to rare cases of life-threatening mesenteric vein thrombosis. The relationship of the symptoms with morbidity and mortality is not clear. Anorexia is related to inflammation, and agneusia and anosmia carry a good prognosis. Psychiatric manifestations may be more common in those with GI affection, inflammation being the common pathogenic factor. Treatment is symptomatic, and proper hygiene precautions are necessary considering the possible fecal shedding of the virus, especially during endoscopic procedures on the GI tract.